Thrive in sunshine, brace for thunder: Least-cost robust power system investments under political shocks - Ali Darudi; Jonas Savelsberg; Ingmar Schlecht (ZBW - Leibniz Information Centre for Economics, 2024)
Energy system planning literature often focuses on either normal operating conditions or on shock/restriction scenarios. Systems designed only for normal years struggle during crises like fuel shortages or trade restrictions, leading to lost load or high prices, while systems optimized entirely for shocks can result in overinvestment in generation technologies with high capital costs. In this paper we address this limitation by incorporating both normal years and shocks in one single optimization model, using a partial equilibrium electricity market. Using Switzerland as the case study, we demonstrate how varying the severity and frequency of shocks affects the optimal technology mix. In the case of Switzerland, robust planning of the generation mix becomes crucial only at trade capacity reduction of more than 70%. When gas import is unavailable during the shock period, liquid fuel becomes optimal in severe trade capacity reduction by 90% or full autarky happening from once in 100 years to once in 10 years. As the frequency of these shocks increase, higher CAPEX technologies, such as renewables, become more favourable, with nuclear emerging as a viable option only if these severe shocks happen every other year. Our findings underscore the importance of balancing cost-efficiency with system resilience to ensure robust energy planning, capable of thriving in normal conditions whilst bracing for stressed conditions.
Keywords: Q40; Q41; C61; 330; System Adequacy; Robust Planning; Energy system resilience; Numerical modelling